γ-AApeptides as a New Strategy for Therapeutic Development - Nimmagadda, Alekhya; Shi, Yan; Cai, Jianfeng (Current Medicinal Chemistry, 2019)
new class of peptidomimetics termed as
Keywords: antimicrobial activity